2022
DOI: 10.1155/2022/2558548
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Score Signature Consisting of Six Immune Genes Predicts Overall Survival in Patients with Lower-Grade Gliomas

Abstract: Background. Lower-grade gliomas (LGGs) are less aggressive with a long overall survival (OS) time span. Because of individualized genomic features, a prognostic system incorporating molecular signatures can more accurately predict OS. Methods. Differential expression analysis between LGGs and normal tissues was performed using the Gene Expression Omnibus (GEO) datasets (GSE4290 and GSE12657). Immune-related differentially expressed genes (ImmPort-DEGs) were analyzed for functional enrichment. The least absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…constructed an immune risk score signature (IRSS) using the LASSO model, and the IRSS included six relevant immune genes that were good predictors of prognosis in LGG patients. Moreover, the immune infiltration results showed that the genetic profile correlated with innate immune cytopenia ( 12 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…constructed an immune risk score signature (IRSS) using the LASSO model, and the IRSS included six relevant immune genes that were good predictors of prognosis in LGG patients. Moreover, the immune infiltration results showed that the genetic profile correlated with innate immune cytopenia ( 12 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…C-index was calculated to evaluate the consistency of real and predicting survival outcomes. To further verify the performance of CCSPI, we compared different risk systems from other studies ( Supplementary Table S2 ) measured by AUCs and C-index ( Zhang et al, 2020 ; Luo et al, 2021 ; Zhao et al, 2021 ; Zhou et al, 2021 ; Wu et al, 2022 ; Zheng et al, 2022 ) in the CGGA validation cohort.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, Gene Expression Profiling Interactive Analysis (GEPIA, http://gepia.cancer-pku.cn/), an online bioinformatics analysis tool (22), was used to explore the mRNA expression of NUP205 in LGG. We collected data from the Gene Expression Omnibus (GEO, https://www.ncbi.nlm.nih.gov/geo/) database to verify the results of the GEPIA database (GSE12657: 13 LGG tissues vs 5 control tissues; GSE21354: 10 LGG tissues vs 4 normal brain tissues; GSE70231: 24 LGG tissues vs 6 normal brain tissues) (23)(24)(25). In the database of The Cancer Genome Atlas (TCGA, https://portal.gdc.cancer.gov/) (26), we collected RNA sequencing data with the corresponding clinical information of 503 patients with LGG and the DNA methylation sequencing data of 511 patients with LGG, which were used to explore the effects of NUP205 on the prognosis, clinicopathological characteristics, regulatory mechanism, and TIME in LGG.…”
Section: Data Collection and Tissue Preparationmentioning
confidence: 99%